ChemInform Abstract: Regioselective Synthesis of Polyheterohalogenated Naphthalenes via the Benzannulation of Haloalkynes. Issue 17 (April 2016) - Lehnherr, Dan; Alzola, Joaquin M.; Lobkovsky, Emil B.; Dichtel, William R.
Abstract: Versatile halide substitution at six of the seven naphthalene positions of 2‐arylnaphthalenes is achieved through the regioselective benzannulation of chloro‐, bromo‐, and iodoalkynes.